Managing marketing communication in a multichannel system - Schultz, Don E. (Henry Stewart Talks, 2008)
Transition from outbound or 'push' system only to 'push-pull system' including inbound or 'pull' communication, Changing business models, Need for demand chains, From product to service branding, Network communication models, Four communication resources, Measurement and evaluation
Archived at 2022/03/17